An Overview of Domestication Potential of Barbus Altianalis (Boulenger, 1900) in Uganda - Aruho, C.; Walakira, J.K.; Rutaisire, J. (Aquaculture Reports, 2018)
Domestication of fish is a key strategy for diversification of farmed species to meet consumer’s choices and demands as well as conservation of the species for sustainable provision of nutrition benefits and incomes. Initial successful induced spawning of Barbus altianalis was achieved, but there is low adoption attributed to lack of sufficient quality seed. This paper reviews the ecological and social-economic trends, and potential prospects that justify the domestication of this high value indigenous species, and identify gaps that could be addressed to increase seed production for commercialization. Review findings show that due to overexploitation, there is a steady decline of B. altianalis in Ugandan water bodies, with no current record from Lake Victoria where catches had in the past been reported. B. altianalis shows ability to survive in interlacustrine-riverine environments although, the juveniles are largely confined in the river or stream water. Varying levels of adaptability and tolerance to environmental conditions including oxygen and temperature by different age groups occur. The species has a great potential for culture as an omnivorous species with high chances of adapting to varying feeding strategies. Knowledge gaps in size at maturity, appropriate inducing hormones, growth conditions, egg hatchability and larvae weaning were identified as key challenges associated with B. altianalis domestication. Understanding the underlying natural ecological dynamics of B. altianalis will guide further research in the areas mentioned to ensure advancement in domestication so as to meet the rising demand for B. altianalis. This will curtail its overexploitation in the wild and also improve the livelihoods of the communities in the region.
Keywords: Cyprinid; Omnivorous; Indigenous species; Domestication; Commercialization